2020
DOI: 10.1590/1678-7757-2020-0269
|View full text |Cite
|
Sign up to set email alerts
|

Dental discoloration caused by Grey-MTAFlow cement: analysis of its physicochemical, biological and antimicrobial properties

Abstract: Dental discoloration caused by Grey-MTAFlow cement: analysis of its physicochemical, biological and antimicrobial properties Tricalcium silicate-based cement are materials used in reparative and regenerative procedures in endodontics. A recently proposed formulation aimed to enhance handling during clinical use with a versatile material applicable by syringe. Although, the use of bismuth oxide as radiopacifier and grey raw powder are drawbacks considering aesthetics. Objectives: Evaluate physicochemical, biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Testing soluble materials-such as reparative endodontic materials-over agar plates seems inappropriate once solubility halos are observed, indicating possible misleading interpretations [34]. Previous studies reported similar observations when testing hydraulic endodontic materials in contact with agar [67,68,75], reporting a limited antimicrobial effect of the reparative endodontic tested materials (Figure 2-Adapted from cited reference [74]); other studies using other methods such as confocal microscopy in contact with dentin and a mature biofilm [84] also concluded that previous disinfection of the site to be treated with these materials is crucial and mandatory in order to expect a positive clinical outcome. Different storage methods for antimicrobial testing can also obtain varying results; in water, for example, ProRoot MTA showed higher antimicrobial activity than when aged in blood and exhibited significant antimicrobial activity reduction after 7 days [35].…”
Section: Hydraulic Calcium Silicate-based Reparative Materialsmentioning
confidence: 79%
See 1 more Smart Citation
“…Testing soluble materials-such as reparative endodontic materials-over agar plates seems inappropriate once solubility halos are observed, indicating possible misleading interpretations [34]. Previous studies reported similar observations when testing hydraulic endodontic materials in contact with agar [67,68,75], reporting a limited antimicrobial effect of the reparative endodontic tested materials (Figure 2-Adapted from cited reference [74]); other studies using other methods such as confocal microscopy in contact with dentin and a mature biofilm [84] also concluded that previous disinfection of the site to be treated with these materials is crucial and mandatory in order to expect a positive clinical outcome. Different storage methods for antimicrobial testing can also obtain varying results; in water, for example, ProRoot MTA showed higher antimicrobial activity than when aged in blood and exhibited significant antimicrobial activity reduction after 7 days [35].…”
Section: Hydraulic Calcium Silicate-based Reparative Materialsmentioning
confidence: 79%
“…The antimicrobial potential of reparative endodontic materials is directly related to their surface of contact, potential alkaline pH, and hydroxyl release [75], as these factors are directly responsible for damage to lipids, proteins, and DNA in the cell membranes of microorganisms [76]. Another antimicrobial mechanism of these materials is the presence of calcium in their composition, which reduces the presence of carbon dioxide in tissues, a molecule which is used by anaerobic bacteria, in addition to their alkaline pH, caused by the hydroxyl ions, which potentially also favors tissue repair [77].…”
Section: Hydraulic Calcium Silicate-based Reparative Materialsmentioning
confidence: 99%
“…The absence of a specific ISO standard for hydraulic calcium silicate-based materials warrants the inclusion of previously reported methods in the general selection of tests, and the use of the ISO 6876:2012 standard (for endodontic sealers) to evaluate new compositions 7,9,11,12,18,25,26,27 such as Bio-C Pulpo. The inclusion of MTT cell culture testing with fibroblasts was used as a preliminary test for subcutaneous animal biocompatibility, considering the principles of the 3Rs (Replacement, Reduction, and Refinement) in research.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major aesthetic complications after pulpotomy with white and grey MTA can be the discoloration of the tooth [ 36 , 37 ]. It is caused mainly by the oxidation of heavy metal oxides (bismuth or iron), and by the interaction between erythrocytes and the unset cement in case of inadequate hemostasis [ 38 , 39 , 40 ].…”
Section: Presentation Of Casesmentioning
confidence: 99%